PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DEPUTI BIDANG PENGEMBANGAN DESTINASI PARIWISATA - Eli Rahayu; Mr Ajimat (Jurnal Ekonomi Efektif, 2018)
This study aims to determine the discipline of the employees of the Secretariat Deputy of Tourism Destination Development Division, to know the performance of employees at the Secretariat staff of Deputy Tourism Destination Development Division, to determine the effect of work discipline on the performance of employees at the Secretariat of Deputy Tourism Destination Development.               The research method used is the method of associative quantitative approach. Methods of data collection conducted in this study with questionnaires questionnaire. Method of determining sample with saturated sample counted 50 employees. Method of data analysis by using Test Validity, Test Reliability, Simple Linear Regression Equation, Simple Correlation, Coefficient of Determination, Significance Test.               Based on the results of data calculations that have been done by the authors, the correlation between the discipline of work on the performance of employees at the Secretariat of Deputy Tourism Destination Development obtained the value of simple linear regression coefficient Y = 44.111 + 0.269 X, meaning that if the compensation salary increased 1% it will affect the increase of employee performance of 0.269% and vice versa if the discipline of work decreased by 1% then there will be a decrease in employee performance of 0.269%. Correlation Coefficient Value r = 0.245 with Weak relationship level. While the calculation result of Coefficient of Determination (KD) contributed the influence of work discipline on the performance of employees at Deputy Secretariat of Tourism Destination Development, R Square value of 6% and the rest 94%. At the significance level of t test 0,05 = 5% Ho accepted and Ha rejected because sig value (0,08> 0,05). But at the level of significance of 10% Ho is rejected and Ha accepted means Ho there is no influence between the discipline of work on the performance of employees in the Secretariat of Deputy Tourism Destination Development and Ha there is influence between work discipline on the performance of employees in the Secretariat of Deputy Tourism Destination Development. Keywords: Work Discipline and Employee Performance